Modelagem e otimização da fermentação alcoólica em batelada alimentada a baixa temperatura - Veloso, Ivan Ilich Kerbauy (2019)
The effect of product inhibition on yeast hinders the production of wine with ethanol concentration above 80.0 g L-1 (~10 °GL) in the industrial ethanol production process commonly performed at 34 °C. Lowering the fermentation temperature is a way to produce wines with higher ethanol contents. In this work, batch fermentations were carried out at temperatures of 28, 30, 32, and 34 °C, with initial substrate concentration of 180.0 g L-1, using industrial yeast under conditions reproducing those found in Brazilian distilleries. The Andrews-Levenspiel hybrid kinetic model, considering viable cells, showed an excellent fit to the experimental data. The model kinetic parameters were used to simulate and optimize fed-batch fermentations at different temperatures, resulting in satisfactory descriptions of the process behaviors. A new optimization strategy to obtain the maximum possible ethanol production, based on the CEmax parameter of the Andrews-Levenspiel kinetic model (Maximum concentration of ethanol after which cell growth ceased), provided ethanol production of up to 134.7 g L-1 (17.1 °GL) at 28 ºC and 305.4 g L-1 substrate. A modification was made to the Andrews-Levenspiel kinetic model, relating the parameter “n” (dimensionless constant related to the toxic potential of the product) to the final ethanol concentration (CEf), in order to enable the model to describe the behavior of fed-batch fermentations performed with high substrate concentration and at temperatures from 28 to 34 ºC. In addition, simulations were carried out with high initial cell concentration to verify the increase of process productivity. The results showed that the original model presented limitations to represent process behavior with high cell concentration in the inoculum, being necessary a readjustment of the model to the experimental data obtaining new values for the kinetic parameters.